Establishing adherence–concentration–efficacy thresholds of TDF–FTC pre-exposure prophylaxis for HIV prevention in African women: a protocol for the Women TDF–FTC Benchmark Study - Wu, Linxuan; Saina, Matilda; Brown, Clare; Chege, David; Donnell, Deborah; Glidden, David V.; Ngure, Kenneth; Mugo, Nelly R.; Akelo, Nina; Schaafsma, Torin; Anderson, Peter L.; Mugwanya, Kenneth K. (Frontiers in Reproductive Health, 2024)
Background: Oral pre-exposure prophylaxis (PrEP) using co-formulated emtricitabine (FTC) and tenofovir disoproxil fumarate (TDF) is a potent HIV prevention method for men and women, with its efficacy highly dependent on adherence. Pivotal HIV efficacy study combined with directly observed pharmacological study defined thresholds for HIV protection in men who have sex with men (MSM) that have been key to PrEP promotion and development of new PrEP agents. For African women at risk for HIV, a priority group due to disproportionately high incident HIV infections, variable adherence in PrEP clinical trials and limited pharmacologic data have resulted in a lack of clarity about PrEP adherence required for HIV protection. We propose a study to quantify the adherenceconcentration-efficacy thresholds of TDF/FTC PrEP among African cisgender women to inform decision about optimal PrEP dosing and adherence for HIV protection.Methods: We will randomize 45 low-risk HIV-uninfected African women 18-30 years old to directly observed TDF/FTC PrEP of: 2, 4, or 7 doses/week for 8 weeks. A complementary age-matched pregnant women cohort at high HIV risk to receive 7 doses/week will be recruited (N=15). The primary aim is to establish benchmark concentrations in dried blood spot (DBS) and peripheral blood mononuclear cells (PBMCs); plasma, whole blood (WB), urine, hair, vaginal fluid, and vaginal tissue (non-pregnant women only) will be archived for future testing. Drug concentrations will be measured using methods validated for each biological matrix. Pharmacokinetic models will be fit to drug concentrations to quantify concentration-adherence thresholds. To define drug concentrations associated with HIV protection, we will apply the newly defined thresholds from the primary pharmacologic trial to the subset of women randomized to TDF/FTC or TDF in the Partners PrEP Study with drug concentration assessed in plasma and WB samples. Multiple imputation will be used to construct a dataset with drug concentrations at each visit when an HIV test was performed for the entire cohort, replicating the work for MSM.The proposed study will generate the first African women-specific TDF-PrEP adherenceconcentration-efficacy thresholds essential to guide the accurate interpretation of TDF/FTC PrEP programs and clinical trials of novel HIV prevention products using TDF/FTC as active control.